Strategic public relations leadership - Gregory, Anne and Willis, Paul (Routledge, 2013)
The strategic contribution of public relations -- A public relations view of the organisation -- Leadership and public relations -- Supporting the chief executive -- A new model of strategic public relations -- The pre-occupations of public relations leaders -- Contextual intelligence -- Valuing values -- The business of ethics -- Enacting the role -- The responsibilities of public relations leaders -- The planner -- The catalyst -- The expert technician -- The internal educator -- The consultant -- Public relations at the edge
https://katalog.adlr.link/Record/0-720030463